Nanocomposites for the desulfurization of fuels - Saleh, Tawfik A. (IGI Global, Engineering Science Reference, 2020)
"This book explores the synthesis, properties, and technological developments of nanomaterials and their applications in petroleum"-- Provided by publisher
Keywords: Fossil fuels -- Desulfurization -- Materials.; Petroleum chemicals -- Desulfurization -- Materials.; Nanocomposites (Materials) -- Industrial applications.; elektronické knihy; electronic books